2019
DOI: 10.3390/ijerph16101698
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Groundwater Quality in CKDu Affected Areas of Sri Lanka: Implications for Drinking Water Treatment

Abstract: This study investigated the water quality of the groundwater that was collected from the chronic kidney disease of unknown etiology (CKDu) prevailing areas in the dry zone of Sri Lanka to assess its suitability for drinking purposes, and for the first time a Water Quality Index (WQI) with emphasis on proposing appropriate drinking water treatment method was developed. A total of 88 groundwater samples were collected in dry (December 2016) and wet (May 2017) seasons; high concentrations of water hardness, fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 35 publications
2
51
1
1
Order By: Relevance
“…Similarly, uoride levels were relatively high in Thunukkai compared to those of the dry zone of Sri Lanka, reported by Chandrajith et al, [25]. Water hardness and the conductivity levels in Thunukkai were compatible with those of the high and moderately prevalent areas [24].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similarly, uoride levels were relatively high in Thunukkai compared to those of the dry zone of Sri Lanka, reported by Chandrajith et al, [25]. Water hardness and the conductivity levels in Thunukkai were compatible with those of the high and moderately prevalent areas [24].…”
Section: Discussionsupporting
confidence: 56%
“…Nevertheless, in compliance with the present study, Wickramarathna et al, [10] reported insigni cant levels of Cd and As in ground water of Girandurukotte, Wilgamuwa and Nikawewa areas. Chloride ion content in the groundwater of Thunukkai was exponentially high compared to the groundwater in CKDu high prevalent areas such as Padaviya, Kebithigollawa, Medawachchiya, & Kahatagasdigiliya, and moderate prevalence areas such as Mihintale, Talawa, and Nochchiyagama of the dry zone of Sri Lanka [24]. Similarly, uoride levels were relatively high in Thunukkai compared to those of the dry zone of Sri Lanka, reported by Chandrajith et al, [25].…”
Section: Discussionmentioning
confidence: 75%
“…However, the heavy metals such as As and Cd in the water of Thunukkai were significantly low compared to the levels detected in the North Central province (Jayasumana et al, 2013(Jayasumana et al, & 2015. Chloride ion content in the ground water of Thunukkai was exponentially high compared to the ground water in CKDu high prevalent areas such as Padaviya, Kebithigollawa, Medawachchiya, & Kahatagasdigiliya, and moderate prevalence areas such as Mihintale, Talawa, and Nochchiyagama of the dry zone of Sri Lanka (Cooray et al, 2019). Water hardness and the conductivity levels in Thunukkai were compatible with those of the high and moderately prevalent areas (Cooray et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…However, the studies toward the effect of water consumption on the incidence rate of CKDu is scarce to date. We examined the chemical quality of groundwater from different CKDu affected zones [12,13] and developed an integrated water quality index (WQI) [13] to demarcate water with high TDS, DOC, and fluoride in CKDu areas that requires treatment [14].…”
Section: Groundwater Quality In Ckdu Areasmentioning
confidence: 99%
“…In this study, a decentralized automated NF-membrane-based pilot drinking-water treatment plant was fabricated to meet the stringent water requirements in a CKDu-affected zone in Sri Lanka. Based on our previous data [14], a suitable NF membrane was selected out of ten commercial brands with the highest TDS and DOC rejection. Then, a drinking-water treatment plant equipped with the selected NF membrane was fabricated and installed in a CKDu-prevalent area of Sri Lanka, and its performance was investigated for one year.…”
Section: Nanofiltration In Drinking-water Productionmentioning
confidence: 99%